PALI1 facilitates DNA and nucleosome binding by PRC2 and triggers an allosteric activation of catalysis - Qi Zhang (Nature Portfolio, 2021)
The polycomb repressive complex 2 (PRC2) is a histone methyltransferase regulating cell differentiation and identity. Here, the authors show that the vertebrate-specific PRC2 accessory subunit PALI1 facilitates substrate binding by the complex and elucidate the allosteric mechanism of PALI1- mediated PRC2 activation.